A critical review of material flow, recycling technologies, challenges and future strategy for scattered metals from minerals to wastes. (20th November 2018) - Zhang, Lingen; Xu, Zhenming
Abstract: Scattered metals play irreplaceable role in some clean energy technologies and advanced materials, and they will become much more important in the future. Global consumption of scattered metals has significantly grown in recent decades. However, at present, imbalances of exploitation, manufacturing and recycling of scattered metals are quite severe resulting in some uncertain supply risk. Hence, securing reliable, ordered and sustainable access to these scattered metals from minerals, functional products to wastes is necessary. This paper focuses on scattered metals in wastes and investigates minerals distribution, material flow, and current recycling technology of scattered metals from minerals to wastes. Especially, for the recycling technology, some representative methods including selective extraction, ion exchange and flotation, precipitation and vacuum metallurgical technology etc, the specific procedures, reagent, optimization and recycling situation of scattered metals were summarized in the review. Meantime, environmental and supply risk, and recycling challenges are expounded in detail. Although these technologies had obtained quite satisfactory results for recycling of a certain scattered metals in wastes, it is no deny that current technologies still have some challenges for further promotion. Overexploitation, disordered mining and the imbalance of the exploitation, production and recycling had also increased supply risk and environmental risk. For recycling technology, the shortages and defects of each technology are discussed from the perspective of technological promotion and environmental protection in the review. Furthermore, future replying strategies for scattered metals from wastes from the perspective of mining governance, environmental and supply sustainability, and technological improvement were proposed. Graphical abstract: Image 1 Highlights: Mineral distribution, material flow and supply of scattered metals are investigated. Current recovery technologies of scattered metals in wastes are reviewed in detail. Environmental risk, supply risks, and challenges for scattered metals are analyzed. Future strategy and recycling perspectives of scattered metals are proposed.